Penerapan Teknik Relaksasi Genggam Jari Terhadap Persepsi Nyeri Pada Pasien Post Operasi Fraktur Di Rsud Dr. Moewardi Surakarta - Febriana Dwi Cahyaningrum; Eska Dwi Prajayanti; Isti Wulandari (STIKes Ibnu Sina Ajibarang, 2024)
Background : A fracture is a broken bone caused by traumatic bone injury and weak physical strength. Based on the World Health Organization (WHO), in 2020 the incidence of fractures is increasing, recording fractures occurring in approximately 13 million people with a prevalence rate of 2.7%. Fractures occurred in approximately 15 million people in 2019. Purpose : To find out the results of the implementation of finger grip relaxation therapy to reduce post-operative fracture pain in Flamboyan Room 7 RSUD Dr. Moewardi Surakarta. Method : This application uses a case study method with a research sample of 2 respondents, research instruments using observation sheets and Visual Analogue Scale (VAS) pain scale measurements. Results : Before the finger grip therapy was given, the patient experienced moderate pain, and after the finger grip therapy was given, the patient experienced a decrease in pain to mild pain. Conclusion : In this application, finger grip therapy has the effect of reducing the pain scale in post-fracture surgery patients.